2002
DOI: 10.1021/ja012747a
|View full text |Cite
|
Sign up to set email alerts
|

Late First-Row Transition-Metal Complexes of Texaphyrin

Abstract: The preparation of first-row transition-metal complexes of texaphyrin, a porphyrin-like, monoanionic penta-aza macrocyclic ligand, is reported. Specifically, the synthesis of organic-soluble Mn(II) (1), Co(II) (2), Ni(II) (3), Zn(II) (4), and Fe(III) (5) texaphyrin derivatives and their water-soluble counterparts (6-10) from appropriate metal-free, nonaromatic macrocyclic precursors is described. It was found that metal cations of sufficient reduction potential could act to oxidize the nonaromatic macrocyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 51 publications
5
61
1
3
Order By: Relevance
“…In all cases, however, the transition-metal complexes of texaphyrins proved much easier to reduce than analogous metalloporphyrins, the difference being more than 500 mV in most cases. [53] Such findings are consistent Figure 11. Front (top) and side (bottom) views of the solid-state structure of 34.…”
Section: Texaphyrin Complexessupporting
confidence: 84%
See 1 more Smart Citation
“…In all cases, however, the transition-metal complexes of texaphyrins proved much easier to reduce than analogous metalloporphyrins, the difference being more than 500 mV in most cases. [53] Such findings are consistent Figure 11. Front (top) and side (bottom) views of the solid-state structure of 34.…”
Section: Texaphyrin Complexessupporting
confidence: 84%
“…(For example, the E 1/2 value for the gadolinium(iii) complex was found to be relatively substituent independent and about À294 mV versus Ag/AgCl when recorded in DMSO in the presence of 0.1m tetrabutylammonium perchlorate. [53] ) Furthermore, and perhaps more importantly, it was found that, once generated, the one-electron-reduced form of texaphyrin, Gd-Tex + C, was capable of reacting with oxygen to form superoxide in a fast, but slightly unfavorable equilibrium process [Eq. (1)].…”
Section: Mechanistic Studies Of Gadolinium(iii) Texaphyrinmentioning
confidence: 99%
“…The spectrum is typical of a high spin (S = 3/2) 3d 7 Co(II) ion, similar to that reported for Co(II) texaphyrin [22] and unlike other Co(II) porphyrins which generally exist as low spin (S = 1/2) complexes [23].…”
supporting
confidence: 79%
“…To date, texaphyrin has proved to be an excellent ligand for a number of transition metal cations [12] and for those of the trivalent lanthanide series [13]. These complexes are potentially interesting as drugs.…”
Section: Discussionmentioning
confidence: 99%